The Impact of Management Commitment on Firm Performance, The Mediating Role of Supply Chain Integration, Practices, and Green Supply Chain Management - Zenia Estella Soesetyo; Hotlan Siagian; Zeplin Jiwa Husada Tarigan (Master of Management, School of Business and Management, Petra Christian University, 2025)
The company's management always strives to enhance competitiveness by making business processes efficient and effective, while also paying attention to environmental protection. This study addresses the impact of management commitment on firm performance through supply chain integration, supply chain practices, and green supply chain management. The study employed a quantitative approach, and data collection was conducted among 80 manufacturing companies in Indonesia. The data were analyzed using partial least squares (PLS) with SmartPLS software version 4.0. The study results indicate that management commitment influences supply chain integration, supply chain practices, and the adoption of a green supply chain approach. Companies can optimize the role of external partners in supply chain integration, thereby influencing supply chain practices and the development of green supply chains. However, this study reveals that supply chain integration did not directly improve firm performance. Moreover, the results indicate that supply chain practices, such as building strategic partnerships and increasing information sharing, cannot directly improve firm performance. The company implements a green supply chain by evaluating environmental care programs, building awareness among customers to use environmentally friendly products, and consistently offering environmentally friendly products, which can improve firm performance. The practical contribution of research provides enlightenment to manufacturing industry practitioners, motivating them to commit to developing employees and enhancing their skills as human capital assets. Theoretical contribution to enriching the theory of the green environment in producing economic and environmental performance.